Gender‐specific anthropometric markers of adiposity, metabolic syndrome and visceral adiposity index (VAI) in patients with obstructive sleep apnea. (9th October 2013) - Mazzuca, Emilia; Battaglia, Salvatore; Marrone, Oreste; Marotta, Anna M.; Castrogiovanni, Alessandra; Esquinas, Cristina; Barcelò, Antonia; Barbé, Ferran; Bonsignore, Maria R.
Summary Obstructive sleep apnea often coexists with visceral adiposity and metabolic syndrome. In this study, we analysed gender‐related differences in anthropometrics according to sleep apnea severity and metabolic abnormalities. In addition, the visceral adiposity index, a recently introduced marker of cardiometabolic risk, was analysed. Consecutive subjects with suspected obstructive sleep apnea (n = 528, 423 males, mean age ± standard deviation: 51.3 ± 12.8 years, body mass index: 31.0 ± 6.2 kg m−2) were studied by full polysomnography (apnea–hypopnea index 43.4 ± 27.6 h−1). Variables of general and visceral adiposity were measured (body mass index, neck, waist and hip circumferences, waist‐to‐hip ratio). The visceral adiposity index was calculated, and metabolic syndrome was assessed (NCEP‐ATP III criteria). The sample included controls (apnea–hypopnea index <10 h−1, n = 55), and patients with mild–moderate (apnea–hypopnea index 10–30 h−1, n = 144) and severe sleep apnea (apnea–hypopnea index >30 h−1, n = 329). When anthropometric variables were entered in stepwise multiple regression, body mass index, waist circumference and diagnosis of metabolic syndrome were associated with the apnea–hypopnea index in men (adjusted R2 = 0.308); by contrast, only hip circumference and height‐normalized neck circumference were associated with sleep apnea severity in women (adjusted R2 = 0.339). These results changed little in patients without metabolic syndrome; conversely, waist circumference was the only correlate of apnea–hypopnea index in men and women with metabolic syndrome. The visceral adiposity index increased with insulin resistance, but did not predict sleep apnea severity. These data suggest gender‐related interactions between obstructive sleep apnea, obesity and metabolic abnormalities. The visceral adiposity index was a good marker of metabolic syndrome, but not of obstructive sleep apnea.